A choice modeling study for a sanitary landfill in Malaysia: case of Kota Bharu, Kelantan - Nik Ab Rahim, Nik Nor Rahimah; Othman, Jamal (Inderscience, 2022)
Environmental impacts from poor landfilling practice have been a long-time concern in Kota Bharu, a populated city in Peninsula Malaysia. This requires a sustainable disposal solution, a sanitary landfill, but such a project can turn into a failure without household demand side information. This study investigated the willingness of households to pay for a sanitary landfill by employing a survey-based method known as choice modelling. This is used to obtain the willingness of households to pay towards the environmental benefits of a sanitary landfill described by attributes of controlled leachate discharge, reduced intensity of bad odour, reduced disease vector and promotion of a scenic view. The resulting estimates show positive willingness to pay for each attribute (ranging from RM2.12 to RM12.61) and for the sanitary landfill (ranging from RM7.62 to RM10.41). The gathered information benefits policymakers to make decisions that match the demands of households so as to avoid the likelihood of opposition and project infeasibility.